Economic Development And Its Measurement - Muhammad Erwin Soaduan Pohan (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2021)
National development seeks to achieve fairly high economic growth, the ultimate goal of which will be to improve the quality of life and welfare for the entire community. Economic growth is interrelated with the process of increasing the production of goods and services in people's economic activities. In other words, growth is a single-dimensional development and is assessed by increasing production output and increasing income. This shows an increase in national income which is reflected by the total number of Gross Domestic Product (GDP). Indonesia, as a developing country, is in the midst of carrying out planned and gradual development, without neglecting the efforts of equity and stability in the face of the Covid-19 pandemic, which has made a number of sources of funds used to maintain public health so that for development and equitable distribution of the people's economy, the government is expected to recover immediately. People's economy slumped. Economic growth is a long-term economic problem and is a fundamental phenomenon in every country today. The process of economic growth has parameters with measurements through GNP, foreign exchange reserves, the balance of payments balance, and others. However, Islam commands humans to uphold justice in all issues related to muamalah, including economic justice. Zakat is one of the pillars in reducing the gap between the rich and the poor. QS At Taubah 60 explains that humans are entitled to receive zakat, the first 4 parties are high priority and the second 4 parties are low priority. Through the Amil Zakat Agency as an official government institution, the portrait of economic inequality can be reduced from year to year. This agency has become a reference for the international community as an innovative and massive agency or institution in helping the people.